ByzRev 05.2023.025: Christopher Star, Apocalypse and golden age.: The end of the world in Greek and Roman thought. Baltimore: Johns Hopkins University Press 2021. - Kraft, András (The Byzantine Review, 2023)
Christopher Star, Apocalypse and golden age: the end of the world in Greek and Roman thought. Baltimore: Johns Hopkins University Press 2021. IX + 320 pp. – ISBN 978-1-42144163-4